2020
DOI: 10.1093/eurheartj/suaa059
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation ablation in heart failure

Abstract: Atrial fibrillation (AF) and heart failure (HF) commonly coexist in the same patient and either condition predisposes to the other. Several mechanisms promote the pathophysiological relationship between AF and HF, reducing quality of life, increasing the risk of stroke, and worsening HF progression. Although restoration and maintenance of sinus rhythm would be ideal for those patients, several trials comparing rhythm and rate control failed to show a benefit of rhythm control strategy, achieved with pharmacolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…Although restoration and maintenance of sinus rhythm would be ideal for these patients, several studies comparing rhythm and rate control have failed to show any advantage of rhythm control achieved with pharmacological therapy in terms of HF hospitalization or death [ 37 , 38 ]. Catheter ablation is an established therapy for symptomatic AF patients who do not respond to medical therapy and have normal cardiac function [ 38 , 39 ]. Furthermore, early rhythm-control therapy has been associated with a lower risk of adverse CV outcomes than usual care among patients with a history of CV disease within the first year of AF diagnosis [ 40 ].…”
Section: Atrial Fibrillation and Hfmentioning
confidence: 99%
See 3 more Smart Citations
“…Although restoration and maintenance of sinus rhythm would be ideal for these patients, several studies comparing rhythm and rate control have failed to show any advantage of rhythm control achieved with pharmacological therapy in terms of HF hospitalization or death [ 37 , 38 ]. Catheter ablation is an established therapy for symptomatic AF patients who do not respond to medical therapy and have normal cardiac function [ 38 , 39 ]. Furthermore, early rhythm-control therapy has been associated with a lower risk of adverse CV outcomes than usual care among patients with a history of CV disease within the first year of AF diagnosis [ 40 ].…”
Section: Atrial Fibrillation and Hfmentioning
confidence: 99%
“…Furthermore, early rhythm-control therapy has been associated with a lower risk of adverse CV outcomes than usual care among patients with a history of CV disease within the first year of AF diagnosis [ 40 ]. Several recent studies have shown improvement in clinical outcomes after AF ablation in HF patients, highlighting the growing importance of the invasive approach in this patient population [ 39 ]. The recent Catheter Ablation vs. Standard Conventional Therapy in Patients with Left Ventricular Dysfunction (CASTLE-AF) trial was the first randomized trial investigating the impact of AF catheter ablation compared with medical therapy (rate or rhythm control) on mortality and hospitalizations in patients with HF.…”
Section: Atrial Fibrillation and Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…Mehrere Mechanismen fördern die pathophysiologische Beziehung zwischen VHF und HI, indem sie die Lebensqualität verringern, das Schlaganfallrisiko erhöhen und das Fortschreiten der HI verschlimmern [26]. Obwohl die Wiederherstellung und Aufrechterhaltung des Sinusrhythmus für diese Patienten ideal wären, konnten mehrere Studien, die Rhythmus-und Frequenzkontrolle verglichen, keinen Vorteil der Strategie der Rhythmuskontrolle, die mit pharmakologischer Therapie erreicht wird, in Bezug auf HI-Hospitalisierung oder Tod zeigen [27]. Die Katheterablation ist eine etablierte Option für symptomatische VHF-Patienten.…”
Section: Vorhofflimmern Und Hiunclassified